Teams Games Tournament with Traditional Marble Game as Instructional Media: Improving Science and Social Studies Learning Outcomes in Indonesian Primary Education - Dhea Febrianti; Juraid Abdul Latief; Rizal Rizal; Nashrullah Nashrullah; Roberto Rolly Bulalong; Surahman Wilade (Papanda Publisher, 2026)
Low student engagement and unsatisfactory learning outcomes in Integrated Science and Social Studies (IPAS) remain persistent challenges in Indonesian elementary classrooms. This study investigates the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by a traditional marble game on the IPAS learning outcomes of fourth-grade students. A quantitative pre-experimental design with a one-group pretest–posttest format was employed. Twenty-eight students from Class IV-A at SD Negeri 24 Palu, Indonesia, participated in the study. Data were collected through a 17-item validated multiple-choice achievement test (α = .905) and classroom observation sheets. Descriptive statistics, normalized gain (N-Gain) analysis, and a paired sample t-test were used to analyze the data. The mean score increased significantly from 50.98 (pretest) to 83.29 (posttest). The mean N-Gain of 0.633 indicated moderate learning improvement. The paired t-test confirmed a statistically significant difference (t(27) = 10.77, p < .001). Classroom observations showed student activity rising from 79% to 95% across two meetings. These findings demonstrate that integrating TGT with culturally familiar game-based media creates an engaging, cooperative learning environment that meaningfully enhances elementary students' cognitive achievement in IPAS, offering a low-cost and contextually relevant instructional alternative for resource-limited settings.